Наскільки стійкими структурами є мутагенні таутомери основ ДНК? - Броварець, О.О.; Говорун, Д.М. (Вiopolymers and Cell, 2010)
Мета. Визначити час життя мутагенних таутомерів основ ДНК, досліджуючи фізико-хімічні механізми їхньої внутрішньомолекулярної таутомеризації. Методи. Неемпірична квантова хімія, аналіз топології електронної густини за Бейдером, фізико-хімічна кінетика. Результати. Вивчено фізико-хімічну природу перехідного стану внутрішньомолекулярної таутомеризації основ ДНК, встановлено час життя мутагенних таутомерів останніх. Висновки. Час життя мутагенних таутомерів основ ДНК на 3–10 порядків перевищує характерний час реплікації ДНК в клітині (~103 с). Це підтверджує адекватність постулату, на якому ґрунтується таутомерна гіпотеза Вотсона-Крика щодо спонтанних транзицій. Їхня висока стійкість обумовлена відсутністю як в основній, так і мутагенній таутомерній формі внутрішньомолекулярних Н-зв’язків. Aim. To determine the lifetime of the mutagenic tautomers of DNA base pairs through the investigation of the physicochemical mechanisms of their intramolecular proton transfer. Methods. Non-empirical quantum chemistry, the analysis of the electron density by means of Bader’s atom in molecules (AIM) theory and physicochemical kinetics were used. Results. Physicochemical character of the transition state of the intramolecular tautome- risation of DNA bases was investigated, the lifetime of mutagenic tautomers was calculated. Conclusions. The lifetime of the DNA bases mutagenic tautomers by 3–10 orders exceeds typical time of DNA replication in the cell (~103 s). This fact confirms that the postulate, on which the Watson-Crick tautomeric hypothesis of spontaneous transitions grounds, is adequate. The absence of intramolecular H-bonds in the canonical and mutagenic tautomeric forms determine their high stability. Цель. Определить время жизни мутагенных таутомеров оснований ДНК, исследуя физико-химические механизмы их внутримолекулярной таутомеризации. Методы. Неэмпирическая квантовая химия, анализ топологии электронной плотности по Бейдеру, физико-химическая кинетика. Результаты. Изучена физико-химическая природа переходного состояния внутримолекулярной таутомеризации оснований ДНК, установлено время жизни мутагенных таутомеров последних. Выводы. Время жизни мутагенных таутомеров оснований ДНК на 3–10 порядков превышает характерное время репликации ДНК в клетке (~103 с). Это подтверждает адекватность постулата, на котором базируется таутомерная гипотеза Уотсона-Крика спонтанных транзиций. Высокая стабильность мутагенных таутомеров обусловлена отсутствием как в основной, так и мутагенной таутомерной форме внутримолекулярных Н-связей.